Exploring the Relations Among Teachers’ Epistemic Theories, Work Engagement, Burnout and the Contemporary Challenges of the Teacher Profession - Lammassaari, Heidi; Hietajärvi, Lauri; Salmela-Aro, Katariina; Hakkarainen, Kai; Lonka, Kirsti (Frontiers in Psychology, 2022)
Current educational reforms concerning curricula and digitalization challenge educators to meet new demands learning and schooling. What is common for current educational reforms is that they tend to emphasize competencies that are not related to the traditional subject-matters and reflect a stance which presents learning as a naturally reflective and collaborative act. It is often assumed that teachers are automatically ready to implement ideas of this kind in practice. In this study, we propose that teachers’ theories about knowledge, knowing and learning, particularly their epistemic theories, may be related to how teachers approach these reforms which challenge their previous ways of working and how they perceive their wellbeing at work. To examine these matters, we explored the dynamic interrelations between teachers’ epistemic theories, conformity with the novel curricular and digital reforms (ideas behind the new curriculum and digitalization program), perceptions of the school leadership, work engagement and burnout. Participants (Study 1 n = 228; Study 2 n = 200) were Finnish class teachers and subject-matter teachers. Both data sets were collected before the COVID-19 pandemic. For data analysis, we plotted correlation network figures. Results showed that if teachers’ epistemic theory was in harmony with the curricular or digital reforms, there is a positive association with work engagement and negative association with burnout. In sum, results of this provided a hint of the phenomenon suggesting that teachers’ epistemic theories may be a factor which buffers teachers to meet the current epistemic and developmental challenges of teachers’ profession, and furthermore, serve as grounds for a positive association for teachers to feel adequate and satisfied in their work.